Quantitative analysis of the impacts of Croatia's agricultural trade policy on the agri-food sector - Peter Weingarten; Klaus Frohberg; Etti Winter; Catrin Schreiber (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2003)
Croatia recently signed several trade liberalisation agreements. The cornerstones of its trade policy are WTO membership, the Stabilisation and Association Agreement with the EU and Croatia's application of membership as well as bilateral free trade agreements within the Stability Pact for South Eastern Europe. The objective of this paper is to quantify the impact of Croatia's agricultural trade policy on the agri-food sector. For the analysis, a partial equilibrium model based on 1999/2000 data is used. Trade between Croatia and Bosnia and Herzegovina, Hungary, Slovenia, the EU-15 and the rest of the world is modelled for 12 product groups. Three liberalisation scenarios are analysed for the years 2002 and 2005. The scenarios differ with regard to the tariff changes. In general, the model results indicate that reciprocal trade liberalisation is welfare improving for Croatia. The increase in consumer welfare is larger than the decline in farmers' profits and the loss of governmental tariff revenues. In conclusion, the continuation of trade liberalisation is to be recommended. However, trade policy alone will not solve the existing problems of the agri-food sector, and transitional compensation measures could be considered to avoid unacceptable hardship. The benefits of trade liberalisation are primarily to be seen in an improved access to international markets, which probably enables Croatian food processors to realise economies of scale. In addition, internationally binding commitments such as trade agreements are likely to foster the internal and international political credibility and reduce political risks. – – In den letzten Jahren hat Kroatien mehrere Handelsabkommen unterzeichnet. Die Hauptelemente der kroatischen Handelspolitik sind die Mitgliedschaft in der WTO, das Stabilisierungsund Assoziierungsabkommen mit der EU und der Antrag auf EU-Mitgliedschaft sowie die bilateralen Freihandelsabkommen innerhalb des Stabilitätspaktes für Südosteuropa. Ziel des vorliegenden Beitrages ist es, die Auswirkungen dieser Agrarhandelspolitik auf den kroatischen Agrar- und Ernährungssektor zu quantifizieren. Für die Analyse wird ein partielles Gleichgewichtsmodell verwendet, das auf Daten der Jahre 1999/2000 basiert. Für 12 Produktgruppen wird Kroatiens Handel mit Bosnien und Herzegowina, Ungarn, Slowenien, der EU-15 und dem Rest der Welt modelliert. Für die Jahre 2002 und 2005 werden drei Liberalisierungsszenarien untersucht, die sich bezüglich der Zolländerungen unterscheiden. Insgesamt zeigen die Modellergebnisse, das eine wechselseitige Handelsliberalisierung wohlfahrtssteigernde Effekte für Kroatien hat. Der Anstieg der Konsumentenwohlfahrt übersteigt den Einkommensrückgang der Landwirte und den Verlust an staatlichen Zolleinnahmen. Daher ist eine Fortsetzung der Handelsliberalisierung empfehlenswert. Allerdings kann die Handelspolitik alleine die existierenden Probleme im Agrar- und Ernährungssektor Kroatiens nicht lösen. Um unerwünschteHärten zu vermeiden, könnten für eine Übergangsphase Kompensationsmaßnahmen in Betracht gezogen werden. Der Nutzen einer Handelsliberalisierung ist vor allem in einem verbesserten Zugang zu internationalen Märkten zu sehen. Dies ermöglicht es kroatischen Verarbeitern wahrscheinlich, Skaleneffekte zu realisieren. Außerdem erhöhen international bindende Verpflichtungen wie Handelsabkommen die interne und internationale politische Glaubwürdigkeit und tragen damit dazu bei, politische Risiken zu reduzieren.
urn:nbn:de:gbv:3:2-23321
Keywords: Q11; Q17; Q18; 330; Croatia; trade liberalisation; agri-food sector; partial equilibrium analysis; Kroatien; Handelsliberalisierung; Agrar- und Ernährungssektor; partielle Gleichgewichtsanalyse; Außenhandelspolitik; Agraraußenhandel; Wirtschaftspolitische Wirkungsanalyse; Agroindustrie; Kroatien